Sensory and consumer profiling of potatoes grown in the USA - Sharma, Chetan (Kansas State University, 2019)
Many studies related to potato sensory qualities are being published in journals focused on agriculture, plant breeding, biochemistry, biotechnology, marketing, food quality and sensory science. The growing number of these publications imply the importance of sensory based findings in achieving desired phenotype markers, consumer product acceptance, advertising claims, etc. It has been established that sensory tests are required and are of prime importance for future direction of research programs. Keeping this view in mind, a study was planned to investigate a number of potato cultivars for sensory language development, sensory profile, consumer liking and attitudinal responses. Potatoes have been a commodity of interest for some time due to nutritional and sensory reasons. Tuber quality traits from aroma, flavor and texture point of view are gaining importance in breeding and processing programs, thus, making it a need to develop a standard lexicon to provide common terminology for use in communicating between breeders, producers, marketers, and researchers. A highly trained panel developed, defined, and referenced a lexicon with 66 attributes using a consensus based descriptive analysis method with 55 cultivars of tubers. Samples were served mashed and air fried. Full lexicon includes five appearance attributes, eighteen aroma attributes, nineteen flavor attributes, twelve texture attributes, four mouthfeel and three aftertaste attributes. The 55 cultivars used for lexicon development were also successfully profiled for the developed attributes. Cooked, cardboard, umami, starchy, salty, metallic, bitter and astringent attributes were mostly common among all samples. Attributes such as vegetable complex, beany, nutty, toasted, sweet potato, eggy and cauliflower were unique to certain cultivars. The underlying construct behind food acceptability was investigated for mashed potatoes. Twelve cultivars of potatoes were tested for sensory profile development by open-ended and check-all-that-apply (CATA) question methodologies. Consumer terminology associated with liking included cooked potato aroma, cooked potato flavor and sweet taste, whereas chemical, unnatural, odorless, flavorless and metallic taste were associated with disliking. Open-ended question was found difficult by 67% of participants for top 3 box responses on 9-point difficulty scale. Grainy, mealy, lumpy, chunky and pasty texture was found disliked by consumers. Compared to open-ended questions, the amount of information composed by CATA method was less and inefficient to describe the samples fully. Hedonic potato liking by consumers was linked to sensory outcomes for the purpose to dissect flavor and texture preferences in the potatoes. The consumers were asked to evaluate liking on hedonic scale for 12 cultivars of potato. Sensory findings were collected by using Consensus-based Descriptive analysis approach for the same cultivars. The cluster analysis identified three subgroups with different overall liking patterns, indicating existing possibilities in the acceptance of wild, flavorful potato cultivars. Drivers of liking were identified for respective groups by using internal preference mapping technique. Dissimilar features were found important in determining hedonic potato likings. Purple Majesty, Masquerade and Rio Colorado cultivars were found most liked by respondents while Russian Banana least. Tuber color, price, cultivar name on package, color of peel and locally produced were found as important factors in purchase-decisions.
Keywords: Sensory; Consumer; Open-end; CATA; Drivers of likingPotato